A study of effectiveness on garbage trap system in urban areas / Mohamad Syah Azrul Mohd Shariff - Mohd Shariff, Mohamad Syah Azrul (Faculty of Architecture, Planning and Surveying, 2013)
Water pollution is a global problem faced by many countries in the region, it is the biggest problem in human life because of the dependence on water resources is high. Water is also an important requirement of the day. Much effort the government has implemented since 1993 until now. Government has also introduced a system of litter traps used to reduce water pollution. Objective of this study was to identify the cause of problems related to the effectiveness of the trap trash and bring awareness to residents and the public about the responsibility to protect the river from pollution because the river is the most important water resources of the country. Data are collected from questionnaire survey, case study and interview on selected projects in order to achieve the objectives. The information and data collected through questionnaires are analysed and presented in table and graph form. From the finding, the biggest problem in implementing the rehabilitation program is the attitude of society. Their lack of civic awareness in protecting rivers, lakes, mines and so on. In solving this problem, the government, the authorities and the public should jointly preserve and protect river and the environment so that it is not contaminated. We should join a program run by the government in protecting the river from pollution and increase civic awareness in themselves.